The Intervening Role of Entrepreneurial Motivation in the Link Between Innovation Education and Entrepreneurial Intentions - Muh. Yahya; Andi Naila Quin Azisah Alisyahbana (Pinisi Journal of Entrepreneurship Review, 2024)
Unemployment poses a significant challenge in Indonesia, exacerbated by the nation's high population growth rate, which intensifies competition in the job market. One of the most effective strategies to address this issue is to encourage entrepreneurship, thereby increasing the number of entrepreneurs who can create new job opportunities. This study aims to explore both the direct and indirect effects of innovation and entrepreneurship education on entrepreneurial intentions, with a particular focus on the mediating role of entrepreneurial motivation. The research utilizes a quantitative approach to examine how innovation and entrepreneurship education influence students' intentions to pursue entrepreneurial careers, and how entrepreneurial motivation serves as a crucial link in this relationship. The study's independent variables are innovation and entrepreneurship education, while entrepreneurial intention is the dependent variable, and entrepreneurial motivation acts as the intervening variable. The research was conducted among Vocational High School students, who represent a key demographic for fostering future entrepreneurs. The findings reveal that both innovation and entrepreneurship education have significant direct and indirect impacts on entrepreneurial intentions, mediated by entrepreneurial motivation. These results highlight the importance of enhancing entrepreneurial motivation as a pivotal factor in transforming educational and innovative inputs into concrete entrepreneurial outcomes. The study underscores the need for educational strategies that not only impart knowledge but also actively engage and motivate students to pursue entrepreneurship, thereby contributing to efforts to reduce unemployment through the creation of new enterprises.